2020
DOI: 10.1111/jar.12736
|View full text |Cite
|
Sign up to set email alerts
|

One social network, two perspectives: Social networks of people with Down syndrome based on self‐reports and proxy reports

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Eight studies documented that regardless of the independence of adults with DS, some required support in going for walks, going to the cinema, staying healthy, seeing a doctor [ 63 , 98 ], emotional support [ 63 ], participation in extracurricular activities [ 95 ], personal care [ 74 , 100 ], handling money [ 88 , 100 ], respite care, using public transport [ 78 , 100 ] and want to continue living with parents [ 64 ]. In three studies, most adults with DS became more independent as they transitioned to adulthood and caregivers recognised the importance to their adults with DS QoL [ 91 , 96 , 98 ]; while one study documented that most mothers did not remember whether young adults with DS played an integral part of the transition process or were actively involved in decision making [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight studies documented that regardless of the independence of adults with DS, some required support in going for walks, going to the cinema, staying healthy, seeing a doctor [ 63 , 98 ], emotional support [ 63 ], participation in extracurricular activities [ 95 ], personal care [ 74 , 100 ], handling money [ 88 , 100 ], respite care, using public transport [ 78 , 100 ] and want to continue living with parents [ 64 ]. In three studies, most adults with DS became more independent as they transitioned to adulthood and caregivers recognised the importance to their adults with DS QoL [ 91 , 96 , 98 ]; while one study documented that most mothers did not remember whether young adults with DS played an integral part of the transition process or were actively involved in decision making [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported that adults with DS were passionate about their friendships and rated them as a major contributor to their sense of social inclusion, acceptance, and self-esteem [ 62 , 63 , 68 , 91 , 95 , 96 , 98 ]. However, some studies reported that adults with DS had few friends [ 63 , 93 ], 40% wanted more friends or had no friends [ 78 , 87 ], whereas other studies found adults with DS had many friends [ 98 ] or made friends easily [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations